2015
DOI: 10.1366/14-07810
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser-Induced Breakdown Spectroscopy Studies of Nitropyrazoles: The Effect of Varying Nitro Groups

Abstract: The technique of femtosecond laser-induced breakdown spectroscopy (FLIBS) was employed to investigate seven explosive molecules of nitropyrazole in three different atmospheres: ambient air, nitrogen, and argon. The FLIBS data illustrated the presence of molecular emissions of cyanide (CN) violet bands, diatomic carbon (C2) Swan bands, and atomic emission lines of C, H, O, and N. To understand the plasma dynamics, the decay times of molecular and atomic emissions were determined from time-resolved spectral data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…The peak wavelengths of the emission bands are 388.34 nm (0-0 band), 387.14 nm ((1-1) band), 386.17 nm ((2-2) band), and 385.46 nm quently the sample molecular structure plays an important role in the atomic emission intensity. 14,18,19 1-NP has the highest percentage of the C atoms among the three samples, and consequently shows the strongest C I emission intensity (Fig. 4a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak wavelengths of the emission bands are 388.34 nm (0-0 band), 387.14 nm ((1-1) band), 386.17 nm ((2-2) band), and 385.46 nm quently the sample molecular structure plays an important role in the atomic emission intensity. 14,18,19 1-NP has the highest percentage of the C atoms among the three samples, and consequently shows the strongest C I emission intensity (Fig. 4a).…”
Section: Resultsmentioning
confidence: 99%
“…1 Rao et al used fs LIBS to investigate how the position and number of the nitro groups affect the molecular emission intensities of seven nitropyrazoles. 18 They also used fs and ns LIBS to investigate the molecular and atomic emissions of seven nitroimidazoles in air and argon atmospheres, and suggested that the intensity ratio of the atomic and molecular emissions can serve as a performance metric for energetic materials. 19 Sreedhar et al studied the molecular and atomic emission spectra of 5-nitro-2,4-dihydro-3H-1,2,4-triazol-3-one (NTO), 1,3,5-trinitroperhydro-1,3,5-triazine (RDX), and octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX) in the atmosphere using ns and fs LIBS, and found that the intensity ratio of CN/C in the fs case was stronger than that in the ns case.…”
Section: Introductionmentioning
confidence: 99%
“…Rao et al performed LIBS research on pyrazole, 1-nitropyrazole, 3-nitropyrazole, 3,4-dinitropyrazole and 1-methyl-3, 4,5 trinitro pyrazole [102,103]. CN molecular fragment bands in the ranges of 357–360 nm, 384–389 nm and 414–423 nm, C 2 Swan bands in the range of 460–475 nm, 510–520 nm and 550–565 nm were observed.…”
Section: Laser-induced Breakdown Spectroscopymentioning
confidence: 99%
“…These molecules are largely investigated using the LIBS technique to quantify organic substances, nitrogen containing explosives, biological and pharmaceutical samples. [20][21][22] In our previous work, the interaction of laser-induced carbon plasma in methane and argon atmospheres has been investigated using optical emission spectroscopy (OES). 23 The time of flight signals of atomic C and molecular C 2 show triple and double peaks respectively in the argon atmosphere in contrast to the methane atmosphere.…”
Section: Introductionmentioning
confidence: 99%